The Association between Mental Health and Job Satisfaction in Nurses Working in Teaching Hospitals Affiliated to Mazandaran University of Medical Sciences in 2016 - Fatemeh norouzi; Masoumeh Bagheri Nesami; zamani (Mazandaran University of Medical Sciences, 2018)
Introduction and purpose: Job satisfaction is a measure of positive feelings and attitudes that people hold about their job. It seems that job  atisfaction is an important factor affecting mental health. We aimed to determine the relationship between job satisfaction and mental health in nurses. Methods: This cross-sectional study was performed in 2016 on 250 nurses in hospitals affiliated to Mazandaran University of Medical Sciences, Iran. Sampling was performed through stratified random sampling method in proportion to the number of nurses in hospital wards. The inclusion criterion was at least one year of work experience in nursing. Data were collected by using the 28-item Mental Health Questionnaire, the standard job satisfaction questionnaire (19 items), and a socio-demographic information form. To analyze the data, descriptive tests, Chi-square test, Pearson correlation coefficient were used in SPSS. Results: The mean of age of the nurses was 31.71±5.83 years. The mental health average score was 19.42±11.49, indicating poor mental health. The mean job satisfaction score was 57.62±10.60, demonstrating very high job satisfaction. There was a significant negative correlation between job  satisfaction and mental health problems, that is, with increasing job satisfaction, mental health problems are reduced (r= - 0.15, P=0.01). Conclusion: According to our results, there was a significant negative correlation between job satisfaction and mental health. In other words, by increasing job satisfaction, mental health disorders can be reduced. Therefore, the results of this study can be used by policy makers to improve the nursing profession and adopt the necessary measures designed to promote job satisfaction.